IMPLEMENTATION OF ACADEMIC SUPERVISION OF ISLAMIC RELIGIOUS EDUCATION DURING THE COVID-19 PANDEMIC - Suhairi Suhairi; Badrudin Badrudin (MANAGERE : Indonesian Journal of Educational Management, 2021)
This study aims to analyze the implementation of academic supervision of Islamic Religious Education supervisors during the covid-19 pandemic at the Ogan Komering Ulu Selatan District Public Middle School. The approach used is descriptive qualitative—data collection through observation, interview, and documentation techniques. The data analysis technique is carried out circularly, starting from data reduction, data display, and conclusion drawing is a data analysis technique carried out. The results showed that the implementation of the academic supervision of the Islamic Religious Education supervisor during the Covid-19 pandemic at the Ogan Komering Ulu Selatan District Public Middle School was carried out online and offline with individual and group techniques. The implementation of academic supervision carried out are activities for fostering Islamic Religious Education (GPAI) teachers, monitoring National Education Standards (SNP), evaluating PAI teacher performance, and carrying out professional guidance and training for PAI teachers. It's just that these activities have not run optimally.